Change the way you persuade - Williams, Gary A (2002)
Notes that executives typically fall into one of five decision-making categories viz. charismatics; thinkers; skeptics; followers; and controllers. Describes each of the five decision-making styles in detail. Presents a hypothetical situation and uses it to demonstrate how a fictional protagonist should best argue her case to her CEO.